Co-aggregation and heritability of organ-specific autoimmunity: a population-based twin study. Issue 5 (May 2020) - Skov, Jakob; Eriksson, Daniel; Kuja-Halkola, Ralf; Höijer, Jonas; Gudbjörnsdottir, Soffia; Svensson, Ann-Marie; Magnusson, Patrik K E; Ludvigsson, Jonas F; Kämpe, Olle; Bensing, Sophie
Abstract : Objective: Co-aggregation of autoimmune diseases is common, suggesting partly shared etiologies. Genetic factors are believed to be important, but objective measures of environmental vs heritable influences on co-aggregation are absent. With a novel approach to twin studies, we aimed at estimating heritability and genetic overlap in seven organ-specific autoimmune diseases. Design: Prospective twin cohort study. Methods: We used a cohort of 110 814 twins to examine co-aggregation and heritability of Hashimoto's thyroiditis, atrophic gastritis, celiac disease, Graves' disease, type 1 diabetes, vitiligo and Addison's disease. Hazard ratios (HR) were calculated for twins developing the same or different disease as compared to their co-twin. The differences between monozygotic and dizygotic twin pairs were used to estimate the genetic influence on co-aggregation. Heritability for individual disorders was calculated using structural equational modeling adjusting for censoring and truncation of data. Results: Co-aggregation was more pronounced in monozygotic twins (median HR: 3.2, range: 2.2–9.2) than in dizygotic twins (median HR: 2.4, range: 1.1–10.0). Heritability was moderate for atrophic gastritis (0.38, 95% CI: 0.23–0.53) but high for all other diseases, ranging from 0.60 (95% CI: 0.49–0.71) for Graves' disease to 0.97 (95% CI: 0.91–1.00) for Addison's disease. Conclusions: Overall, co-aggregation was more pronounced in monozygotic than in dizygotic twins, suggesting that disease overlap is largely attributable to genetic factors. Co-aggregation was common, and twins faced up to a ten-fold risk of developing diseases not present in their co-twin. Our results validate and refine previous heritability estimates based on smaller twin cohorts.